Crisis of Reason in Contemporary World: Post Modern Trends of Techno-Instrumental Reason and of Universal Liberal Model (Looking Back or Looking Forward?) - Torrão, Fernando (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2015)
We advocate through this piece of work a mainly philosophical-political reflection onto the overcoming of the rational liberal model which characterized the Western way of thinking in the Modern Age (from the Age of Enlightenment onward), caused by the dawn of –as many put it- postmodern times, which, through deconstructionist methods reject the great narrative from the past, diminishing the importance of the supposedly absolute «truths». However, is it truly a step forward of civilization to proclaim –following Horkheimars footsteps- or the «decline of reason»?
Keywords: Liberalism; Reason; Postmodernity; Universality.